Supporting Multiple Smart-City Applications based on MUSANet, a Common IoMT Middleware - Meslin, Alexandre Malheiros; Rodriguez, Noemi de La Rocque; Endler, Markus (Anais do Workshop em Clouds e Aplicações (WCGA); 2020: Anais do XVIII Workshop em Clouds e Aplicações, 2020)
The MUSANet system is a three-tier middleware for smart cities implemented using InterSCity, ContextNet, and Mobile-Hub. In order to decentralize processing from the cloud, the system includes stationary layer processing in the fog and collection of mobile data in the edge. In this article, we explore the flexibility and decoupling offered by MUSANet. We present two different applications for smart cities and discuss how they can be implemented in MUSANet, showing that, using the basic infrastructure, we can build new applications without interfering in existing ones due to the low coupling between the entities that make up the tiers of MUSANet. A third application illustrates how the distribution of data processing among MUSANet layers can help reduce the network load, preserving energy.